Wpływ rekultywacji leśnej terenów pokopalnianych na wybrane właściwości gleb inicjalnych na przykładzie zwałowiska nadkładu Kopalni Węgla Brunatnego Turów S.A. - Nietrzeba-Marcinonis, Jolanta
The thesis aim was to evaluate the changes in the initial soil properties during the forest reclamation of the post - open mine soil-less grounds in "Turów" Lignite Open Mine, Joint Stock Company. The research included the outer dumping ground with area of ca. 2175 ha. Simultaneously, the argument of the efficiency of that reclamation direction of the specific soil-less grounds for creation of functional soil cover in respect of the environment and cultivation was examined. In order to verify the stated argument, limited, regional and laboratory examination was performed.
Keywords: rekultywacja leśna bezglebowych gruntów pokopalnianych; gleby inicjalne